2019
DOI: 10.1091/mbc.e18-11-0694
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting nanobodies and Affimers for superresolution imaging in light microscopy

Abstract: Antibodies have long been the main approach used for localizing proteins of interest by light microscopy. In the past 5 yr or so, and with the advent of superresolution microscopy, the diversity of tools for imaging has rapidly expanded. One main area of expansion has been in the area of nanobodies, small single-chain antibodies from camelids or sharks. The other has been the use of artificial scaffold proteins, including Affimers. The small size of nanobodies and Affimers compared with the traditional antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…These findings indicated that CEA binding Affimers have better sensitivity and specificity than the corresponding antibody. This could be due to their being physically smaller than antibodies (~ 3 nm for Affimer vs. ~ 14 nm for IgG) facilitating better penetration into fixed cells 14 , 30 .
Figure 2 Cell binding and selectivity of anti-CEA Affimers on LoVo cells in comparison to monoclonal antibody.
…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that CEA binding Affimers have better sensitivity and specificity than the corresponding antibody. This could be due to their being physically smaller than antibodies (~ 3 nm for Affimer vs. ~ 14 nm for IgG) facilitating better penetration into fixed cells 14 , 30 .
Figure 2 Cell binding and selectivity of anti-CEA Affimers on LoVo cells in comparison to monoclonal antibody.
…”
Section: Resultsmentioning
confidence: 99%
“…These small proteins are ~10kDa in size, and can be specifically dye-labelled using a unique cysteine placed at either the N-or the Cterminus. This places the dye molecule close to the target protein [3], reducing 'linkage error'. The small size of the Affimer additionally improves its ability to penetrate dense structures over antibodies [2].…”
Section: Maryland United Statesmentioning
confidence: 99%
“…Rather large size and multivalence of antibodies, however, limit their application as labeling agents in imaging approaches. Over the past years, the popularity of antigen-binding fragments of antibodies and single-chain nanobodies derived from camelids or shark antibodies grew vastly ( Beghein and Gettemans, 2017 ; Carrington et al., 2019 ; Leslie, 2018 ). Both types of molecules are much smaller than full-length antibodies, yet possess similar binding properties to their target proteins ( Harmsen and De Haard, 2007 ; Sahl et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%